1982
DOI: 10.1002/ajpa.1330570310
|View full text |Cite
|
Sign up to set email alerts
|

A nonparametric distance analysis of biochemical genetic data from the Åland Islands, Finland

Abstract: Biochemical genetic data from 3272 individuals from the Aland Islands, Finland, are analyzed using a recently developed set of nonparametric genetic distance measures. These measures are more robust than the traditional methods used in previous studies of this population. While there was general agreement in the results of the traditional and nonparametric approaches, some important differences were seen. In these cases, the nonparametric methods gave result more congruent with population history, geographic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1982
1982
1992
1992

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Excluding individuals not born in Aland, Sottunga was also shown to have the most divergent gene frequencies of any parish (Mielke et al, 1976). Others have shown that, although Sottunga received few immigrants from Aland's other parishes, immigrants from Sweden and Finland came in numbers that effectively offset drift effects on gene frequencies after 1900 Carmelli and Jorde, 1982). Including immigrants from outside Aland, Sottunga's gene frequencies were shown to be similar to Aland's main island region by 1929.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Excluding individuals not born in Aland, Sottunga was also shown to have the most divergent gene frequencies of any parish (Mielke et al, 1976). Others have shown that, although Sottunga received few immigrants from Aland's other parishes, immigrants from Sweden and Finland came in numbers that effectively offset drift effects on gene frequencies after 1900 Carmelli and Jorde, 1982). Including immigrants from outside Aland, Sottunga's gene frequencies were shown to be similar to Aland's main island region by 1929.…”
Section: Introductionmentioning
confidence: 95%
“…Sottunga is one of 16 Lutheran parish subdivisions that have been treated in previous studies of Wland's population structure, demography, and regional genetic variation (Eriksson et al, 1971a-c;Mielke et al, 1976Mielke et al, , 1982Workman and Jorde, 1980;Carmelli and Jorde, 1982;Jorde et al, 1982). More detailed descriptions of Aland's population can be found in those papers; relevant details are recapitulated only briefly here.…”
Section: Introductionmentioning
confidence: 99%
“…Sottunga had the largest average genetic distance from other parishes based on three generations of gene frequency data from Alanders (Eriksson et al, 1973). Sottunga's unusual frequencies of Rh and ABO alleles distinguished it from other parishes (Mielke et al, 1976;Eriksson et al, 1980;Carmelli and Jorde, 1982). Its outlier status, particularly in earlier periods, has been attributed to its distance from the main island region and scant immigration from other parishes.…”
mentioning
confidence: 99%
“…Population genetic studies in the &and Islands have demonstrated that isolated outer island parishes have experienced substantial genetic drift (Eriksson et al 1973a, b, Mielke et al 1976, Workman & Jorde 1980, Carmelli & Jorde 1982. Sottunga in particular experienced high rates of drift because of its small population size and low migration rates.…”
Section: Discussionmentioning
confidence: 99%